Application of NCRP 156 Wound Model and ICRP 67 Systemic Plutonium Model for Analysis of Urine Data from Simulated Wounds in Nonhuman Primates. Issue 1 (July 2016) - Poudel, Deepesh; Guilmette, Raymond A.; Konzen, Kevin; Krage, Eric S.; Brey, Richard R.
Abstract : Abstract: The predictions of the wound model described in NCRP Report No. 156, coupled with the systemic model described in ICRP 67, were compared with the actual urinary excretion data and wound retention data from nonhuman primates injected intramuscularly or subcutaneously with 238 Pu(IV) citrate. The results indicated that the early behavior of 238 Pu(IV) citrate in wounds can be adequately described by the default retention parameters for moderately retained radionuclides suggested by the report. The urinary excretion rates after 200 d post intake could not be described well by the parameters of any of the default wound models because of the differences in the systemic handling of plutonium by humans compared to nonhuman primates.